PENGAWASAN DINAS PERHUBUNGAN DALAM PELAKSANAAN UJI KIR TERHADAP ANGKUTAN KOTA DI KABUPATEN KARAWANG - Sofi Nur Rohmah; Hanny Purnamasari; Lolita Deby Mahendra Putri (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
This research is motivated by the continued discovery of public transportation in Karawang Regency operating without proof of passing the periodic motor vehicle inspection (KIR test) and the low compliance of vehicle owners with the mandatory testing. In addition, research on the supervision of the Transportation Agency in the implementation of KIR tests on public transportation is still limited, especially those linking supervision to transportation safety and the environment. This study aims to analyze the supervision of the Transportation Agency in the implementation of periodic motor vehicle testing on public transportation in Karawang Regency. The method used is a qualitative case study approach. Data collection was conducted through interviews, observation, and documentation, while data analysis used an interactive analysis model. The results of the study indicate that supervision still faces various obstacles, such as limited supervision in the field, the persistence of vehicles that do not meet roadworthiness standards, and the enforcement of sanctions that are not optimal. The novelty of this research lies in the focus of the study of the supervision of city transportation KIR tests using George R. Terry's supervision theory linked to aspects of transportation safety and the environment. This study concludes that increased supervision, strict enforcement of sanctions, and continuous socialization are needed to improve vehicle owner compliance with the implementation of KIR tests.